2020
DOI: 10.1074/jbc.ra119.010707
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 preferentially binds and collaborates with the transcription factor RUNX1 to repress AML1–ETO–dependent transcription in t(8;21) AML

Abstract: In up to 15% of acute myeloid leukemias (AMLs), a recurring chromosomal translocation, termed t(8;21), generates the AML1–eight–twenty-one (ETO) leukemia fusion protein, which contains the DNA-binding domain of Runt-related transcription factor 1 (RUNX1) and almost all of ETO. RUNX1 and the AML1–ETO fusion protein are coexpressed in t(8;21) AML cells and antagonize each other's gene-regulatory functions. AML1–ETO represses transcription of RUNX1 target genes by competitively displacing RUNX1 and recruiting cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…ChIP-qPCR after knockdown of ERG revealed an increase in P300 and a decrease in HDAC1 occupancy at the promoter region of RUNX1-RUNX1T1 25 . Furthermore, a recent study has demonstrated that RUNX1 is a component of the NCoR-HDAC3 complex in t(8;21) AML and collaboratively represses RUNX1-RUNX1T1-dependent transcription, thereby linking HDAC3 directly to leukemogenesis associated with t(8;21) 62 . Taken together, the enhanced apoptosis observed in SKNO1 cells following HDAC3 inhibition could be explained by a co-regulatory function of ERG and the NCoR-HDAC3 complex in t(8;21) leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP-qPCR after knockdown of ERG revealed an increase in P300 and a decrease in HDAC1 occupancy at the promoter region of RUNX1-RUNX1T1 25 . Furthermore, a recent study has demonstrated that RUNX1 is a component of the NCoR-HDAC3 complex in t(8;21) AML and collaboratively represses RUNX1-RUNX1T1-dependent transcription, thereby linking HDAC3 directly to leukemogenesis associated with t(8;21) 62 . Taken together, the enhanced apoptosis observed in SKNO1 cells following HDAC3 inhibition could be explained by a co-regulatory function of ERG and the NCoR-HDAC3 complex in t(8;21) leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The FASTQ files were aligned to the mm10 mouse reference genome and subsequently analyzed using HOMER software, as previously described. 40 Cell Culture and Luciferase Assays. HepG2 cells were purchased from ATCC and maintained in Gibco Advanced MEM media supplemented with 10% FBS (Gemini Bio) and L-glutamine (Gibco) at 37 °C with 5% CO 2 , as previously described.…”
Section: Materials Availability Statementmentioning
confidence: 99%
“…Inhibition of HDAC1 and HDAC2 leads to down-regulation of RAD51, BRCA1, and CHK1, which are crucial for the DNA damage response (DDR) and subsequent DNA double-strand break and apoptosis in AML cell lines. And AML-1-ETO can bind with HDAC1, 2, and 3 to repress the AML1 target genes in t (8,21) AML ( 123 ). And HDAC6 deacetylates the chaperone Hsp90, eliciting the interaction with AML1-ETO protein, which can be dissociated by HDAC inhibitors that mediates the degradation of AML1-ETO protein.…”
Section: Hdacs In Aml With Aml1-etomentioning
confidence: 99%